Immunobiotic Lactobacillus jenseni TL2937 alleviates dextran sodium sulfate-induced colitis in mice - Islam, M. Aminul (2019)
Immunobiotics have emerged as promising interventions to alleviate inflammatorydamage in inflammatory bowel disease (IBD). However, the beneficial properties of immunobioticsare strain dependent and therefore, each strain has to be evaluated in order to demonstrate itspotential application in IBD. Lactobacillus jensenii TL2937 attenuates gut acute inflammatoryresponse triggered by Toll-like receptor 4 activation. However, its effect on colitis has not beenevaluated before.Objectives: the aim of this work was to study whether the TL2937 strain was able to protect againstthe development of colitis in a dextran sodium sulfate (DSS)-induced mouse model.Methods: L. jensenii TL2937 was administered to five-week-old female BALB/c mice before (4 days)the induction of colitis, at a dose of 108 cells/mouse/day. Untreated mice were used as controls.Colitis was established by the administration of 2.5% (w/v) DSS in drinking water for 7 days. Micewere examined daily during 18 days for body weight, general appearance, stool consistency, and thepresence of fecal blood. In addition, myeloperoxidase activity and cytokine production wereevaluated in colon tissue samples.Results: Mice fed with L. jensenii TL2937 had lower disease activity index and alterations of colonlength when compared to control mice. In addition, reduced myeloperoxidase activity, lowerproduction of pro-inflammatory (TNF, IL-1, IL-8, MCP-1, IL-15 and IL-17) and higher levels ofimmunoregulatory (IL-10 and IL-27) cytokines were found in TL2937-treated mice. These findingsindicate that L. jensenii TL2937 is able to alleviate DSS-induced colitis and suggest a novel applicationfor this probiotic strain.